Meningococcal A conjugate vaccine coverage in the meningitis belt of Africa from 2010 to 2021: a modelling study. (February 2023) - Bender, Rose G.; Shen, Jasmine; Aravkin, Aleksandr; Bita Fouda, André Arsène; Bwaka, Ado M.; Galles, Natalie C.; Haeuser, Emily; Hay, Simon I.; Latt, Anderson; Mwenda, Jason M.; Rogowski, Emma L.B.; Sbarra, Alyssa N.; et al.
Summary: Background: As of the end of 2021, twenty-four countries in the African meningitis belt have rolled out mass campaigns of MenAfriVac®, a meningococcal A conjugate vaccine (MACV) first introduced in 2010. Twelve have completed introduction of MACV into routine immunisation (RI) schedules. Although select post-campaign coverage data are published, no study currently comprehensively estimates MACV coverage from both routine and campaign sources in the meningitis belt across age, country, and time. Methods: In this modelling study, we assembled campaign data from the twenty-four countries that had introduced any immunisation activity during or before the year 2021 (Benin, Burkina Faso, Burundi, Cameroon, Central African Republic, Chad, Côte d'Ivoire, Democratic Republic of the Congo, Ethiopia, Eritrea, the Gambia, Ghana, Guinea, Guinea Bissau, Kenya, Mali, Mauritania, Niger, Nigeria, Senegal, South Sudan, Sudan, Togo and Uganda) via WHO reports and RI data via systematic review. Next, we modelled RI coverage using Spatiotemporal Gaussian Process Regression. Then, we synthesized these estimates with campaign data into a cohort model, tracking coverage for each age cohort from age 1 to 29 years over time for each country. Findings: Coverage in high-risk locations amongst children aged 1–4 in 2021 was estimated to be highest in Togo with 96.0% (95% uncertainty interval [UI] 92.0–99.0), followed by Niger with 87.2% (95% UI 85.3–89.0) and Burkina Faso, with 86.4% (95% UI 85.1–87.6). These countries had high coverage values driven by an initial successful mass immunisation campaign, followed by a catch-up campaign, followed by introduction of RI. Due to the influence of older mass vaccination campaigns, coverage proportions skewed higher in the 1–29 age group than the 1–4 group, with a median coverage of 82.9% in 2021 in the broader age group compared to 45.6% in the narrower age group. Interpretation: These estimates highlight where gaps in immunisation remain and emphasise the need for broader efforts to strengthen RI systems. This methodological framework can be applied to estimate coverage for any vaccine that has been delivered in both routine and supplemental immunisation activities. Funding: Bill and Melinda Gates Foundation .